EVOLUTION OF GENDER EQUALITY LAWS IN INDIA: LEGAL PROTECTIONS AND THEIR IMPACT ON WOMEN’S RIGHTS IN THE 21ST CENTURY - Narang, Inderpreet Kaur (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This research paper aims to investigate how gender equality laws have evolved and evaluate how they affect women’s rights in the twenty-first century. Though obstacles still exist, women’s legal rights have been progressively acknowledged over the past few decades. Legislative changes, legal protections, and the larger social setting that have moulded women equality will be discussed in this work. This paper will critically assess the efficacy of these legal clauses in enhancing gender equality by means of case studies, an overview of international frameworks, and legal landscape analysis of many countries. The study will also highlight flaws in the legal system and propose suggestions for improving women's legal protections. Gender equality, a long-standing issue of significant social, political, and legal debate, continues to demand attention and reform within the legal framework. Particularly in areas like education, employment, health, and political involvement, women all around have endured persecution, discrimination, and inequality over the centuries. In the field of gender equality laws, nevertheless, the twenty-first century has witnessed notable advancement. Empowering women and challenging historical gender stereotypes have largely depended on the establishment of legal systems designed to protect women’s rights and promote gender equality. The development of gender equality laws is investigated in this paper together with the legal protections that have evolved in the twenty-first century and their effect on women’s rights. From labour laws to reproductive rights and the fight against gender-based violence, this article shows how legal reforms have changed the terrain for women, so promoting more gender equity in the modern era. As a dynamic democracy, India has made great progress toward gender equality particularly with regard to legislative changes meant to strengthen women's rights. Affected by constitutional clauses and an increasing body of case law, the Indian legal system has moulded the terrain for women in the twenty-first century. Although great progress has been made, the road toward complete gender equality is long still. Whether in the workplace, in personal events like marriage and inheritance, or in relation to protection from violence, the legal protections accessible to women have changed constantly. Court rulings, particularly in historic decisions, have been quite important in advancing women’s rights and combating gender-based discrimination. This paper investigates the development of gender equality laws in India, stressing case laws that have molded the legal defenses given to women in the twenty-first century.